Neurexan prescription is associated with lower risk of sleep disorder recurrence and depression prevalence as compared to Z-drugs and benzodiazepines: a retrospective database analysis in Germany - Hajak, Göran; Vetter, Céline; Wehling, Martin (Healthcare, 2024)
Real-world evidence on the association between natural medicinal products and the recurrence of sleep disorders is currently limited, particularly when compared to the evidence reported for prescription hypnotics. In a retrospective cohort analysis, we investigated patients with sleep disorders prescribed either the natural medicinal product Neurexan (Nx4), benzodiazepines, or nonbenzodiazepines (Z-drugs) using the IQVIA Disease Analyzer database, which encompasses electronic medical records nationwide in Germany. A 1:1 matching procedure based on age, sex, prevalent depression, anxiety or adjustment disorder, and the number of medical consultations in the past 12 months resulted in four cohorts: patients prescribed Nx4 were matched with those prescribed Z-drugs (two cohorts with 8594 matched patients each), and another cohort of patients prescribed Nx4 were matched with those prescribed benzodiazepines (7779 matched pairs). Results from multivariable-adjusted Cox regression models demonstrated that Nx4 was associated with a significantly lower risk of recurrent sleep disorder diagnosis within 30-365 days after prescription compared to both Z-drugs (HR = 0.65, 95%CI = 0.60-0.70, p < 0.001) and benzodiazepines (HR = 0.85, 95%CI = 0.79-0.93, p < 0.001). Additionally, Nx4 was associated with a lower prevalence of depression compared to Z-drugs (HR = 0.90, 95%CI = 0.83-0.98, p = 0.020) and benzodiazepines (HR = 0.89, 95%CI = 0.82-0.97, p = 0.009). These findings suggest an association between Nx4 and improved sleep and mental health outcomes. However, due to inherent limitations in the study design, the causality of this relationship cannot be stated.